The Association of the GABRP Polymorphisms with Systemic Lupus Erythematosus - Hun-Soo Kim; Eun-Heui Jin; Ji-Su Mo; Hyeok Shim; Shin-Seok Lee; Soo-Cheon Chae (Journal of Immunology Research)
Gamma-aminobutyric acid receptor subunit pi (GABRP) is involved in inhibitory synaptic transmission in the central nervous system. This gene encodes multisubunit chloride channels and is also expressed in numerous nonneuronal tissues such as the uterus and the ovaries. This study was aimed to validate whether the polymorphisms in the GABRP gene are associated with the susceptibility to systematic lupus erythematosus (SLE). The genotype frequencies of the rs929763, rs732157, and rs3805455 of the GABRP gene in SLE patients were significantly different from those of the control group (P<0.0001, P=0.05 and 0.002, resp.). Additional analysis showed that the genotype of the rs929763 and rs3805455 of the GABRP gene were also significantly associated with female SLE patients (P<0.0001, P=0.005, resp.). Two haplotype frequencies including a major haplotype of GABRP SNPs were more significantly different between the SLE patients and the healthy controls (P=0.038 and 4.2E-24, resp.). These results suggest that the polymorphisms in the GABRP gene might be associated with the susceptibility to SLE and the haplotype of GABRP SNPs is useful genetic marker for SLE.